A efetividade da Contadoria Judicial Unificada (Cojun) do Tribunal de Justiça do Estado do Tocantins a partir da perspectiva dos sujeitos e da produtividade - Rodrigues, Arthur Emílio Galdino De Sousa (Universidade Federal do Tocantins, 2020)
The present study sought to analyze the performance of the Unified Judicial Accountancy (COJUN) of the Tocantins State Court of Justice in the light of the efficacy and effectiveness of Human Rights in the jurisdictional provision of Tocantins, explaining the role of the Judicial Accountant, what are its functional and social impacts of the profession in different legal systems with emphasis on the country, describing the process of creation and implantation of COJUN, in order to verify the repercussions in its different dimensions in the Tocantinense Judiciary, in deference to the procedural speed and the reasonable duration of the process in the Judicial Accountants of the State of Tocantins, data and documents were compared, demonstrating what are the advantages and disadvantages of COJUN, the reports obtained at COJUN were analyzed, identifying possible biases, presenting in an objective, clear and precise way possible changes in procedures and routines of job, which may be ratified by the GeneralJusticeInternal Affairsof the State of Tocantins in order to achieve excellence in the jurisdictional provision in the Judicial Accountants of the State of Tocantins, of the works presented by COJUN and the enforcement of Human Rights.